(3ahGFO GdTjN CHj HcQ jYbhH Hf CMeO GdUjQais - (3QhGjI CHh GdbGSe RGgQ Hf WGgQ Hf eMeO GdTMGeis
(3ChdgG (B:s
(3CNHQfG CHh eSde GdeDjO Hf YHO GdQMje Yf CHj MGRe , bGd (B: (3cfJ Nda CHj gQjQI hgh jJhVC ddUdGI , acGf jeO jOg MJi jHdY EHWjg s
(3BNQgG (B:s
(3ef TYQ GdYJHi jQKi GHfg (B: (3ajG CSai Ydjc hWhd Thbi Edjc dh Cf PGc jQO TjkG s
(3GdfSNI HgG MhGTs
(3gPg GdfSNI LRA efJbi ef KdGKg GLRGA HBNQgG bQGAg Ydi GdMGaX VjGA GdOjf eMeO Hf YHO GdhGMO GdebOSi Sfg (B634 (3hSeGYGJ CNQi Sfg (B641676 (3Ke SeGYGJ ef GdfSNI Gdefbhd efgGs
(3JHUQI GdYfhGf (B:s
(3QhGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B40 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B179s
Keywords: (3GdeLGejYs